Multi, Inter, and Transdisciplinary Approaches in Islamic Education Learning at SDIT Robbani Banjarbaru: A Field Case Study - Nina Arifa; Husnul Yaqin; Ridhahani Fidzi; Syaifuddin Sabda (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This article discusses the implementation of multidisciplinary, interdisciplinary, and transdisciplinary approaches in Islamic Education learning in Islamic Elementary Schools. Through a case study at SDIT Robbani Banjarbaru, this research aims to identify the practice of integrating Islamic knowledge and values in a holistic learning process. A qualitative method with a case study approach was used to deeply explore the dynamics of teachers, students, and the learning strategies implemented. The results of the study indicate that the integrative approach is able to encourage integration between religious knowledge and general knowledge, as well as shape students' character spiritually, intellectually, and socially. Furthermore, this study found that the application of multidisciplinary, interdisciplinary, and transdisciplinary approaches encourages the creation of a contextual, active, and enjoyable learning atmosphere. Teachers not only act as transmitters of knowledge, but also as facilitators, motivators, and role models who internalize Qur'anic values in each subject. In this way, students not only acquire cognitive knowledge but also experience the process of developing morals and life skills relevant to the challenges of the modern era.